Mix Design of Cementitious Basecourse - Yeo, Yang sheng; Jitsangiam, Peerapong; Nikraz, Hamid (Australian Geomechanics Society, 2011)
Selecting stabilisation mix designs for basecourse materials to provide adequate resistance against damage under traffic and environmental loading is important in maximizing the life of a pavement. Cement stabilised pavements are unique materials that they exist at the border between structural soil and conventional concrete. The pavement layer are typically roller-compacted and thus require sufficient water content to achieve compaction but at the same time also requires water sufficient for cement hydration and workability with a grader. A literature review combined with simple tests are undertaken to determine fit for purpose design mix, i.e. a compaction test to ascertain the optimum moisture content (OMC) and maximum modified dry density (MMDD) and unconfined compressive strength (UCS) test. The tests showed that the MMDD for the material at various cement content are a constant, and a fit for purpose design chart can be developed based on the water and cement content. The OMC for compaction of cement treated basecourse is the OMC of the parent material + 0.25% for every 1% in cement content. This relationship between water content and cement content runs parallel to the minimum water required for effective hydration to take place, i.e. a w/c ratio of 0.25.